The effectivity of mindfulness-based art therapy application-based artificial intelligence on the mental health of pregnant women - Dhanio, Yeyen Wulandari; Runjati, Runjati; Suwondo, Ari; Kurnianingsih, Kurnianingsih; Sudiyono, Sudiyono (Universitas Muhammadiyah Purwokerto, 2023)
Background: The COVID-19 pandemic has become a new stressor with significant pregnancy consequences, limiting access to health services. Mindfulness-Based Art Therapy (MBAT) has been proven to intervene in the body-mind-soul and improve mental health problems. However, no research has developed it into a form of artificial intelligence for use by pregnant women in supporting the current situation of access to health services.Purpose: This study aims to produce a system of MBAT based on artificial intelligence for early detection and to prove the effectiveness of improving mental health in pregnant women.Methods: This study employed Research & Development consisting of 4 stages, namely Literature Study, Development Stage, Validity Expert, and Trial.Results: The MBAT application has five features, from mental health information to history. The validity score of the application system is 87.33%. The trial results showed that the application effectively reduces stress levels by 91.26% and anxiety by 90.24%. Also, the application can predict the percentage reduction in stress and anxiety levels correctly and without errors using the decision tree.Conclusion: This application is helpful for pregnant women and health workers in detecting stress and anxiety levels early in pregnancy and improving mental health.